(3cJGH GdMjOIs - (3YHO GdYRjR Hf jMji Hf YHO GdYRjR GdcfGfj Gdecj, CHhGdMSf,J (B240 (3g` s ((3YHO GdYRjR Hf YHO Gddg Hf eMeO Hf SdjeGf Hf YGeQ s)
(3ChdgG (B:s
(3bGd YHO GdYRjR Hf jMji Hf YHO GdYRjR Hf eSde Hf ejehf GdcfGfi EJUd Hi hCfG HecI eG bO CXgQg HTQ Hf ZjGK GdeQjSi ef Gdbhd HNdb GdbQBf hZjQg s
(3BNQgG (B:s
(3Cf CTQM gPG cdg deG JNhaJ Ydi faSi eeG bO dMbfi HYO gPG GdeLdS hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3Ydi UaMI GdYfhGf JQLeI ddeDdas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B29s
Keywords: (3GdJhMjO hGdedd hGdfMds